2019
DOI: 10.4194/2618-6381-v20_1_04
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Composition of Fillets of African Catfish, Clarias gariepinus Fed with Various Oil-Based Diets

Abstract: This study evaluated effects of diets containing different vegetable oil resources on growth performances, body compositions and fatty acid profile of Clarias gariepinus. The oils were incorporated at 7% level of the diet. Fingerlings were randomly stocked at 20 fish per floating net-hapa (1m 3) and fed the experimental diets for 12 weeks. Fatty acid methyl esters and proximate compositions were determined. Growth performances revealed that fish fed palm oil-based diets yielded best. Fatty acids profile reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…As a result, the concentration of liquid smoke and immersion duration did not affect the fat content of sausages because the liquid smoke compounds could not dissolve non-polar fat. The fat content of smoked sausages was not highly different [25], which found that the fat content of African catfish sausages was in the range of 12.08 -15.94% dw.…”
Section: Fat Content Of African Catfish Smoked Sausagementioning
confidence: 89%
“…As a result, the concentration of liquid smoke and immersion duration did not affect the fat content of sausages because the liquid smoke compounds could not dissolve non-polar fat. The fat content of smoked sausages was not highly different [25], which found that the fat content of African catfish sausages was in the range of 12.08 -15.94% dw.…”
Section: Fat Content Of African Catfish Smoked Sausagementioning
confidence: 89%
“…Lipid deposits were observed in Clarias gariepinus after the addition of palm oil in the diet [14]. Other studies have shown that diets containing large amounts of fat lead to changes in body composition characterized by an increase in body fat accompanied by a decrease in the water content [34,35]. This could explain the observed decrease in the function of increasing the fat content of food distributed moisture content.…”
Section: Discussionmentioning
confidence: 99%
“…Sapu-sapu fish contains 16.85±4.35% crude fat, higher than the fish meal of 10% (Applegate and Angel 2014), catfish 2.1-3.8% (Gökoğlu and Yerlikaya 2015), catfish Africa (Clarias gariepinus Burchell, 1822) of 9.3±0.3% (Effiong and Yaro 2019). The amount of variation in the nutritional content of these fish is influenced by species, individual, age, sex, environment, and season (Gökoğlu and Yerlikaya 2015;Merdzhanova et al 2021;Koca et al 2023).…”
mentioning
confidence: 99%